Thoughts on news media’s role in Nepal’s democratic process - Brand, Sten T (Bodhi: An Interdisciplinary Journal, 2010)
This paper explores media's role in the wake of the 2008 Constituent Assembly (CA) Election in Nepal. The paper will first discuss some important concepts within the field of political science, and then it will move on to incorporate communication theory. After underlining the concepts, the paper will focus on one particular research study focusing on access to information and how this relates to attitude and knowledge among villagers ahead of the 2008 CA election. Finally it will discuss the findings and conclusion. DOI: 10.3126/bodhi.v3i1.2810 Bodhi Vol.3(1) 2009 p.35-43